Evaluation of Suitable Substrate for Seedling Tuber Production by True Potato Seed through Nursery Raising - M.M.R. Jamro,; A.N. Shah,; G.M. Laghari,; A.S. Chandio ,; M.S. Depar, (Journal of Basic & Applied Sciences, 2016)
To determine the suitable substrate, five growth substrates viz. Soil + Sand, Soil + FYM, Soil + Sand + FYM, Soil + PM (Poultry manure) and Soil + Sand + PM were used to grow the three true potato seed (TPS) genotypes viz. TPS-9802, TPS-9804 and TPS-9805. Results of the interactive effect of genotypes x substrates on plant and tuber traits concluded that maximum germination (90.5 %), plant height (46.3 cm), micro tubers (212.7), small tubers (45.7), medium tubers (28.2), large tubers (10.2) and total tubers (296.8), maximum weight of micro (1491 g), small tubers (757.6 g), medium tubers (828.9 g), large tubers (483.7 g) and total tuber weight (3561) per unit area (1m-2) and total tuber yield (35.6 t ha-1) were found in TPS-9804 grown in the substrate of soil+sand+FYM. However TPS-9805 yielded (32.5 t ha-1) and ranked 2nd with same substrate. Hence, it is recommended for raising TPS nursery.